1993
DOI: 10.1021/ma00058a003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and polymerization of 7-alkoxycarbonyl-7-cyano-1,4-benzoquinone methides

Abstract: 7-(Alkoxycarboiiyl)-7-cyano-l,4-benzoquinone methides 4 with four kinds of alkoxy groups, methyl, ethyl, isopropyl, and butyl, were successfully prepared as pure, isolable crystals. Acid-catalyzed 1,6-addition reactions of 7-cyano-7-(ethoxycarbonyl)-1,4-benzoquinone methide (4a) with phenol and NJfdimethylaniline each gave 1:1 adducts in quantitative yield. Compound 4a reacted with hydrogen chloride to give a 1,6-addition product in situ in quantitative yield, but it did not react with acetic acid. When dissol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 9 publications
(28 reference statements)
2
35
0
Order By: Relevance
“…4 Therefore, firstly, we carried out anionic polymerizations of 1 with various organolithium initiators to investigate its anionic polymerization reactivity. The results of the asymmetric anionic polymerizations of 1 with complexes of organolithium reagents with a chiral ligand of (À)-sparteine ((À)-Sp) in dichloromethane at À78 C are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Therefore, firstly, we carried out anionic polymerizations of 1 with various organolithium initiators to investigate its anionic polymerization reactivity. The results of the asymmetric anionic polymerizations of 1 with complexes of organolithium reagents with a chiral ligand of (À)-sparteine ((À)-Sp) in dichloromethane at À78 C are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2 However, the substitution of hydrogen atoms on the exomethylene carbon of the QM with electronaccepting substituents such as cyano and/or ester groups or with electron-donating substituents such as phenyl and dithioethylene groups reduces reactivity and makes them isolable monomers as crystals at room temperature: for example, 7,7-dicyano-1,4-benzoquinone methide, 3 7-(alkoxycarbonyl)-7-cyano-1,4-benzoquinone methides, 4 7,7-bis(alkoxycarbonyl)-1,4-benzoquinone methides, 5 7,7-diphenyl-1,4-benzoquinone methide, 6 7-cyano-7-phenyl-1,4-benzoquinone methide, 7 4-(1 0 ,3 0 -dithiolan-2 0 -ylidene)-2,5-cyclohexanedien-1-one, 8 and 2,6-dimethyl-7-phenyl-1,4-benzoquinone methide. 9 The polymerization behaviors of these isolable QMs have been investigated, and we found that the radical and anionic polymerizations and the solid-state polymerizations of many QMs take place between the substituted exomethylene carbon atom and exocabonyl oxygen with formation of stable aromatic structure to afford the polymers with characteristic main-chain structure, poly(oxy-1,4-phenylene-substituted methylene)s, 4,5,7,9,10 and that the polymerizations of some substituted QMs are a typical equilibrium polymerization involving a considerable degree of depolymerization. 11 Moreover, we reported spontaneous alternating copolymerization of nonhomopolymerizable substituted quinone methides with styrene and p-methoxystyrene, and the spontaneous initiation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, introduction of electron-accepting and/or electron-donating substituents on the exomethylene carbon of the QM reduces its reactivity, leading to isolable monomers as crystals at room temperature: e.g., 7,7-dicyano-1,4-benzoquinone methide [10], 7-(alkoxycarbonyl)-7-cyano-1,4-benzoquinone methides [11], 7,7-bis(alkoxycarbonyl)-1,4-benzoquinone methides [12], 7,7-diphenyl-1,4-benzoquinone methide [13], 4-(1 0 ,3 0 -dithiolan-2 0 -ylidene)-2,5-cyclohexanedien-1-one [14], and 2,6-dimethyl-7-phenyl-1,4-benzoquinone methide [15]. The polymerization behaviors of these isolable QMs have been investigated, and it was found that the radical and anionic polymerizations of QMs take place between the substituted exomethylene carbon atom and exocarbonyl oxygen with formation of stable aromatic structure to afford the polymers, poly(oxy-1,4-phenylene-substituted methylene)s [11,12,15,16]. As QMs having two different substituents on the exomethylene carbon are regarded as prochiral monomers, many asymmetric carbons might be generated in the main chain of the polymers through the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of substituents to the exocyclic carbon or quinonoid skeleton of QM reduces its reactivity and makes it an isolable monomer as a crystal. For example, 7,7‐dicyano‐1,4‐benzoquinone methide,2, 3 7‐(alkoxycarbonyl)‐7‐cyano‐1,4‐benzoquinone methides,3–5 7,7‐bis(alkoxycarbonyl)‐1,4‐benzoquinone methides,6 7,7‐diphenyl‐1,4‐benzoquinone methide,7 and 7‐cyano‐7‐phenyl‐1,4‐benzoquinone methide8 have already been synthesized and isolated. Previously, we investigated the polymerization behavior of these isolable QMs and found that the radical and anionic polymerizations of many QMs take place between the substituted exomethylene carbon atom and exocarbonyl oxygen with the formation of a stable aromatic structure to afford polymers with characteristic main‐chain structures, such as poly(oxy‐1,4‐phenylene‐substituted methylene).…”
Section: Introductionmentioning
confidence: 99%